Analisis Islamic Corporate Governance dalam Meningkatkan Kinerja Lembaga Amil Zakat, Infaq dan Shadaqah Muhammadiyah (Lazismu) Bondowoso - Isnani, Rofiqoh Nur; Fadah, Isti; Shulthoni, Moch. (UPT Penerbitan Universitas Jember, 2025)
The purpose of this research is to explore the implementation of the principles of Islamic Corporate Governance and analyze the implementation of the principles of Islamic Corporate Governance in improving the performance of the Muhammadiyah Amil Zakat, Infaq and Shadaqah Institution in Bondowoso Regency. Implementation of Islamic Corporate Governance by analyzing the principles in it, namely the principles of transparency, accountability, responsibility, independence, justice and sharia compliance. In this study, the informants were the President Director, Director of Fundraising and Cooperation, Director of Empowerment and Distribution and Director of Finance and Assets of Lazismu Bondowoso. The research method used in this research is qualitative with a case study approach. The results of this study are first, the mechanism for implementing Islamic Corporate Governance by Lazismu Bondowoso has generally been implemented but not fully. Because, there are some shortcomings in several aspects of accountability and transparency. Second, the application of Islamic Corporate Governance aspects, namely transparency, accountability, responsibility, independence, fairness, sharia compliance, has a positive impact on improving the performance of Lazismu Bondowoso.